CENTRAL BANK DIGITAL CURRENCY (CBDC) AND THE DYNAMICS OF CHINESE ECONOMIC SHORTCUT TO US DOLLAR HEGEMONY - CHIMA, CHRISTIAN CHUKWUKA; ANTHONY, INWEREGBU ONYEKACHI; EMMANUEL, OBIAH MMADUBUIKE (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
The paper examined central bank digital currency (CBDC) and the dynamics of Chinese economic shortcut to US dollar hegemony. The study employed secondary data to achieve the objectives, in other words, it is a qualitative study. The study revealed that the introduction of Chinese digital RMB (e-CNY) and its advancement in cross-border payments will largely challenge the global hegemony of the US dollar. This move will reduce the costs of trade, facilitate financial inclusion, foster financial innovation and expand the monetary and fiscal components. It will increase payment transparency and decrease money laundering and tax evasion. The study recommended that, there should be a provision of a level playing ground for accessibility and infrastructure that promotes motivation and competition among different payment service providers. There should also be a robust digital architecture that includes optimal, reliable and affordable internet connectivity and comprehensive access to digital devices